MARITIME SAFETY PSYCHOLOGY: POLITICAL AND ETHICAL DIMENSIONS OF SAFETY CULTURE IN MARITIME ORGANISATIONS (Psychology Travelogs, 2025)
Psychological factors play a critical role in maritime accidents, with the human element associated with 80.1% of investigated incidents (2014-2023). Despite technological progress, safety culture in maritime organisations remains insufficiently developed. This study investigates psychological aspects of safety culture through political and ethical dimensions. Research shows 58.4% of accidents relate to human actions, whilst 49.8% of contributing factors concern human behaviour. Three interconnected levels were identified: individual, interpersonal, and organisational. Positive safety culture with organisational commitment achieves necessary safety levels through shared values, effective communication, and mutual trust. Leadership serves as a key catalyst for change, whilst technology creates new psychological risks.
Keywords: maritime safety; human factor; safety culture; safety policy; ethical aspects of management